2018
DOI: 10.3233/adr-180068
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Cerebrovascular Response to a Language Task from the Addenbrooke’s Cognitive Examination in Cognitive Impairment: A Feasibility Functional Transcranial Doppler Ultrasonography Study

Abstract: Background:The incidence of dementia is predicted to rise rapidly, but sensitive diagnostic tests remain elusive. Changes in cerebral blood flow velocity (CBFv) can occur at an early stage of cognitive decline, and can be measured by transcranial Doppler ultrasonography (TCD).Objective: The aim of this study was to characterize the CBFv changes that occur in healthy older adults (HC), mild cognitive impairment (MCI), and Alzheimer’s disease (AD), in response to a language task from the Addenbrooke’s cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…From previous studies in our group, Beishon et al . (2018) demonstrated a significant decrease of CBFV at sustained response during a language task in Alzheimer’s disease but not in MCI when compared with healthy controls [ 19 ]. Although the mean of repeated task presentations to each patient might provide more robust estimates of the CBFV changes [ 83 , 84 ], combining the use of fTCD with other modalities (EEG or near infrared spectroscopy) may enhance discriminatory power in clinical NVC studies [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From previous studies in our group, Beishon et al . (2018) demonstrated a significant decrease of CBFV at sustained response during a language task in Alzheimer’s disease but not in MCI when compared with healthy controls [ 19 ]. Although the mean of repeated task presentations to each patient might provide more robust estimates of the CBFV changes [ 83 , 84 ], combining the use of fTCD with other modalities (EEG or near infrared spectroscopy) may enhance discriminatory power in clinical NVC studies [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…fTCD has multiple advantages in terms of low-cost, high temporal resolution, portability to the bedside and non-harmful repetitive studies. Therefore, current TCD applications have been adopted to study a wide range of conditions such as sickle cell disease [ 13 ], ischaemic [ 14 ] or haemorrhagic [ 15 ] stroke, brain stem death [ 16 ], intraoperative monitoring [ 17 ], cerebral microembolism in right-to-left cardiac shunt [ 18 ], and cognitive impairment [ 19 ], including cerebral pressure autoregulation [ 20 ] and neuroactivation [ 21 ]. The quantification of the NVC response has been assessed by CBFV changes (ΔCBFV), induced by neural stimulation [ 12 , 22 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…De-coupling of these processes has been shown to occur in animal models of AD (Girouard and Iadecola, 2006 ). Human studies have demonstrated conflicting findings of both increased (Corriveau-Lecavalier et al, 2019 ), and decreased (Beishon et al, 2018 ) vascular responses to cognitive stimulation. These opposing findings may reflect compensatory mechanisms occurring early in the disease process, vs. the failure of these mechanisms at later stages (Merlo et al, 2019 ).…”
Section: The Neurovascular Unit In Dementiamentioning
confidence: 99%
“…Despite an increasing proportion of the population living with dementia, there are surprisingly few diagnostics and treatments available. Dementia can cause uncoupling of the NVC processes described above, resulting in an impaired hyperaemic response when individuals are cognitively challenged [ 4 , 23 ]. The observed reduction in CBF [8] and NVC results in a mismatch between CBF demand and supply, leading to cognitive dysfunction [14] .…”
Section: Introductionmentioning
confidence: 99%